Adsorption studies of molybdate(VI)–99Mo onto nano zirconium hydroxide gel. (March 2022) - Ramadan, H.E.; El-Amir, M.A.; Mostafa, M.
Abstract: Zr(OH)4 gels have been prepared by sol-gel method using isoamyl alcohol/ammonia mixture of different concentrations. The nano Zr(OH)4 gel obtained using 80% isoamyl alcohol and diluted ammonia (6%) gave the highest 99 Mo distribution coefficient. SEM images indicated a jelly-like appearance of the optimum Zr(OH)4 gel. XRD analysis proved that Zr(OH)4 gel is an amorphous material. HRTEM analysis indicated a particle size of ≤100 nm with the existence of particle aggregates. According to DLS studies, the hydrodynamic diameter was found to be 78.82 nm (with a mean number percentage of 21.1%), while zeta potential was found to be 29.2 mV N2 adsorption/desorption chromatographic analysis calculations stated a BET surface area of 151 m 2 /g and an average pore diameter of 1.93 nm. Molybdate(VI)– 99 Mo adsorption process onto the optimum Zr(OH)4 gel was found to follow pseudo 2nd order and (to some extent) film diffusion mass transfer kinetic models. The adsorption isotherm was found to follow Langmuir model. From kinetic and adsorption isotherm studies it could be determined that the optimum Zr(OH)4 gel has E a, ΔH° and ΔS° values of 31.29, 50 and 0.185 kJ/mol, respectively, in addition to ΔG° values of −5.09, −7.86 and −11.56 kJ/mol at 25, 40 and 60 °C, respectively. Static molybdate(VI)– 99 Mo capacity (determined from Langmuir adsorption model) was found to be 292.4, 333.3 and 357.1 mg/g at 25, 40 and 60 °C, respectively, while dynamic capacity was found to be 134.3 mg/g at 25 °C. Highlights: Nano zirconium hydroxide gel was prepared via a simple sol-gel method using a mixture of isoamyl alcohol and ammonia. The prepared gel was characterized by different analytical methods. Adsorption studies of 99 Mo on the optimum prepared gel revealed a high static and a fair dynamic adsorption capacities of molybdate(VI)– 99 Mo. The use of the optimum zirconium hydroxide gel as a bed for 99 Mo/ 99m Tc chromatographic column generator gave promising results.